Senior meets junior digital natives: TESLians integrating technology in their teaching practice - Loo, Kien Men; Noordin, Nooreen (Australian International Academic Centre, 2019)
The younger generations of students called Digital Natives learn via technology. The Malaysia Education Blueprint 2013-2025 has taken the initiatives to implement Information and Communication Technology (ICT) in learning in bid to cater to their learning styles. However, the implementation has not been smooth-sailing as most teachers have not been integrating ICT in their lessons seamlessly. Goldberg’s (1981) Big Five Model of Personality can explain various usage of ICT based on their respective trait but TESL (Teaching English as Second Language) undergraduates in the Malaysian context had not been studied before. The researcher purposively selected 72 TESL undergraduates from the Faculty of Educational Studies in a public university in Malaysia for the study using a questionnaire and semi-structured interview. The findings reported high levels of ICT integration and motivation in integrating it. Next, they scored the highest in Openness to experience towards ICT integration in L2 teaching while low in Neuroticism. There was also a statistically significant, moderate, positive relationship between their level of motivation, Agreeableness, Conscientiousness, Extraversion and Openness traits and their ICT integration in L2 teaching. These findings present vital implications for TESL program and course coordinators to facilitate their pre-service teachers to leverage ICT in their teaching practice.